Diverse Roles of NETosis in the Pathogenesis of Lupus - Wang, Meiying; Ishikawa, Tatsuya; Lai, Yupeng; Nallapothula, Dhiraj; Singh, Ram Raj (Frontiers in Immunology, 2022)
NETosis is a form of neutrophil cell death during which extracellular fibrillary structures composed of cytosolic and granule proteins assembled on scaffolds of decondensed chromatin, called neutrophil extracellular traps (NETs), are released. NETs normally contribute to host immune defense. Accumulating evidence implicates aberrant NET production and/or reduced NET clearance, along with alterations of molecules involved in NETosis pathway, in humans and animals with lupus. The extruded nuclear antigens released by NET are a source of autoantigens, which can contribute to the breakdown of self-tolerance in lupus. Excessive NET can also promote the production of pro-inflammatory cytokine interferon-α, elicit direct cytotoxic effect on various renal cells, and cause capillary necrosis and podocyte loss. Additionally, NET can induce endothelial-to-mesenchymal transdifferentiation, which can promote activated myofibroblasts leading to extracellular matrix production. Thus, aberrant NETosis can play diverse roles, including autoantibody production, inflammation, and tissue damage, at different stages of lupus pathogenesis. Evidence suggests that treatments currently used in lupus may reduce NETosis, suggesting a potential utility of targeting NETosis to treat lupus. In fact, several approaches are being experimented to therapeutically target pathways of NETosis. Future studies should precisely delineate different roles of NETosis at different stages of lupus pathogenesis in humans, which would offer a rational basis for NETosis-targeting treatments in the clinic.